2002
DOI: 10.1111/j.1574-6968.2002.tb11064.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental investigation of potentially pathogenicVibrio parahaemolyticusin the Seto-Inland Sea, Japan

Abstract: Seawater and organic material (live and/or dead matter deposited on any substratum submersed in seawater) were collected during the cool weather season from a coast of the Seto-Inland Sea, Japan, and analyzed to determine Vibrio parahaemolyticus densities and the occurrence of pathogenic strains, defined as those possessing tdh and/or trh genes by the polymerase chain reaction (PCR), using isolated DNA from enrichment culture of the samples. About 95% of the samples were positive for V. parahaemolyticus (with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(39 citation statements)
references
References 27 publications
(24 reference statements)
1
37
0
1
Order By: Relevance
“…Vibrios cultured from environmental samples commonly lack the genes coding for proteins with associated pathogenic functions in humans and marine animals (e.g., tdh in V. parahaemolyticus ) (Deepanjali et al, 2005; Canizalez-Roman et al, 2011; Gutierrez West et al, 2013). However, few studies have reported the presence of the tdh and trh genes in V. parahaemolyticus strains of environmental origin; only 0–6% of the samples analyzed from the coasts of the U. S. (Kaysner et al, 1990; Depaola et al, 2000), Europe (Hervio-Heath et al, 2002), and Asia contained the tdh and/or trh genes (Vuddhakul et al, 2000; Wong et al, 2000; Alam et al, 2002). Most of the environmental strains are known to be KP-negative, and only 1–2% of the samples are KP-positive (Joseph et al, 1982; Nishibuchi and Kaper, 1995).…”
Section: Pathogenic V Parahaemolyticusmentioning
confidence: 99%
“…Vibrios cultured from environmental samples commonly lack the genes coding for proteins with associated pathogenic functions in humans and marine animals (e.g., tdh in V. parahaemolyticus ) (Deepanjali et al, 2005; Canizalez-Roman et al, 2011; Gutierrez West et al, 2013). However, few studies have reported the presence of the tdh and trh genes in V. parahaemolyticus strains of environmental origin; only 0–6% of the samples analyzed from the coasts of the U. S. (Kaysner et al, 1990; Depaola et al, 2000), Europe (Hervio-Heath et al, 2002), and Asia contained the tdh and/or trh genes (Vuddhakul et al, 2000; Wong et al, 2000; Alam et al, 2002). Most of the environmental strains are known to be KP-negative, and only 1–2% of the samples are KP-positive (Joseph et al, 1982; Nishibuchi and Kaper, 1995).…”
Section: Pathogenic V Parahaemolyticusmentioning
confidence: 99%
“…Although the gastroenteritis may be self-limited, the infection can cause septicemia that is life-threatening to those with a preexisting medical conditions (Su and Liu, 2007). In Japan, V. parahaemolyticus is responsible for 20–30% of all food poisoning cases (Alam et al, 2002) and is the common cause of seafood-borne illness in many Asian countries (Koralage et al, 2012; Yu et al, 2013). V. parahaemolyticus has also become the leading agent of human gastroenteritis associated with seafood consumption in the United States (Newton et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of tdh and/or trh expression among environmental V. parahaemolyticus isolates is typically <1%, but this may depend on location, sample source and detection method (Kaysner et al, 1990; Alam et al, 2002; Cook et al, 2002; Hervio-Heath et al, 2002; Martinez-Urtaza et al, 2008b). For example, between 49 and 78% of the sediment, water, or oyster samples from Willapa Bay (WA, U.S.) contained trh + V. parahaemolyticus (Kaysner et al, 1990).…”
Section: Introductionmentioning
confidence: 99%